Perbandingan Kualitas Produk Sayur dan Buah pada Pasar Tradisional dan Pasar Modern di Kota Serang dalam Penerapan Strategi Pamasaran - Khaeruman Khaeruman; Hafidz Hanafiah (Majalah Ilmiah Bijak, 2019)
Agricultural products are types of products that have disadvantages, among others: perishable and short shelf life, especially for horticulture. These weaknesses cause horticultural products to require special treatment from pre-harvest to post-harvest so that the quality does not decrease. A decrease in product quality will affect its sale value in the market. However, special handling requires additional costs, so the amount of post-harvest handling must also consider the demand of the buyer.This research aims to find out and understand the best storage treatment for fruits and vegetables to maintain the physical condition of the products and marketing strategies in traditional and modern markets.Based on the results of research shows that most of the people of Serang City tend to prefer shopping in traditional markets, but most also choose to shop in traditional and modern markets, in their opinion it can be concluded that if they shop at traditional markets they can bargain from prices that have been set and they can also directly, whereas if in the modern market they can only see the prices available on the desired goods.